Adoption of alternative fuel vehicle fleets – A theoretical framework of barriers and enablers. (November 2020) - Mohammed, Layla; Niesten, Eva; Gagliardi, Dimitri
Highlights: We develop a theoretical framework on barriers and enablers of adoption by firms. We review 53 articles on the adoption of alternative fuel vehicles by firms. Firms adopt for efficiency, environmental, economic, and strategic gains. We identify operational, economic, knowledge, and organisational policy barriers. The impact of policy and emotions and their interaction requires further research. Abstract: This paper synthesises and analyses factors affecting firms' adoption of Alternative Fuel Vehicles (AFVs). Our theoretical framework on Firm Adoption of Sustainable Technologies (FAST) integrates several technology adoption models with the attribute of 'perceived risk'. On the basis of the FAST theoretical framework, we review and analyse 53 studies on the adoption of AFV fleets. We find that the primary enablers for firms to adopt are linked to efficiency, environmental, economic, and strategic gains. The primary barriers to adoption are limited knowledge, organisational policies, as well as operational and economic factors. Overall, the AFV fleet adoption literature suggests that large firms are more likely to become early adopters, which is largely due to their willingness to accept financial risks in exchange for first mover advantages. We suggest further research avenues particularly on policy and emotions and on the linkages between these two factors.